Implementasi Sengketa Objek Tanah Bersadarkan Pasal 153 jo SEMA Nomor 7 Tahun 2001 Tentang Pemeriksaan Setempat (Studi Putusan Nomor 4/Pdt.G/2021/PN.Mjl): Implementation of Land Object Disputes Based on Article 153 in conjunction with SEMA Number 7 of 2001 Concerning On-Site Inspections (Study of Decision Number 4/Pdt.G/2021/PN.Mjl) - Nuraeni, Yeni; Rani Dewi Kurniawati; Zuraidah (Jurnal Ilmiah Penegakan Hukum, 2025)
Local or on-site investigation is a function determined by law for a judge or panel of judges, which increases the judge's confidence in the clarity of the main case on earth before making a decision. local verification is usually carried out by going directly to the field to prove that the plaintiff is correct in filing his claim. the study aims to determine the implementation of local control in the case of PN decision Number 4/Pdt.G/2021/PN.Mjl, to determine and analyze efforts and obstacles in implementing local control. the research method used is normative-empirical. a library field study is research conducted directly with research subjects through books or literature and direct interviews. the conclusion of the local examination was carried out by the jury, deputy clerk, and related parties. according to the circular of the supreme court of the republic of indonesia, local examinations can be carried out on items that are portable but difficult to bring into the courtroom. Number 7 of 2001. considering this, it can be concluded that local investigations are carried out according to procedural law and based on the principle of rapid decision-making, namely the principle of simple and inexpensive testing, which aims to make decisions.